2007
DOI: 10.1093/cvr/cvm025
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning enhances cell survival and differentiation of stem cells during transplantation in infarcted myocardium

Abstract: We conclude that PC with the chemokine SDF-1 suppresses MSCs apoptosis, enhances their survival, engraftment, and vascular density, and improves myocardial function via SDF/CXCR4 signaling. Chemokine PC is a novel approach for enhancing stem cell survival and regeneration of infarcted myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(208 citation statements)
references
References 36 publications
5
199
0
4
Order By: Relevance
“…After myocardial infarction and reperfusion, reactive oxygen species (ROS) are generated in the ischemic myocardium and directly cause apoptosis. The in vivo oxidative stressinduced apoptosis can be simulated in vitro by H 2 O 2 treatment of both isolated adult cardiomyocytes and MSCs (Kumar and Jugdutt, 2003;Pasha et al, 2008). In the present study, we have shown that SDF-1 pretreatment can protect MSCs from H 2 O 2 -induced damages.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…After myocardial infarction and reperfusion, reactive oxygen species (ROS) are generated in the ischemic myocardium and directly cause apoptosis. The in vivo oxidative stressinduced apoptosis can be simulated in vitro by H 2 O 2 treatment of both isolated adult cardiomyocytes and MSCs (Kumar and Jugdutt, 2003;Pasha et al, 2008). In the present study, we have shown that SDF-1 pretreatment can protect MSCs from H 2 O 2 -induced damages.…”
Section: Discussionsupporting
confidence: 53%
“…Although SDF-1 pretreatment improved cell survival and differentiation (Joo et al, 2004;Pasha et al, 2008), the mechanism has not been well elucidated. Previous studies suggested that cell survival and proliferation are mediated through activation of the signaling cascades PI3K/Akt and MAPK/ERK (Choi et al, 2008;Zhang and Cai, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscles were identified immunohistochemically using antibodies against α-smooth muscle actin (M0951, DAKO). Myocytes were identified with α-sarcomeric actin antibody (Sigma) and 4â€Č, 6-diamino-2-phenylindole (DAPI, Sigma) was used to stain nuclei [12]. Fluorescent imaging was performed with an Olympus BX41 microscope (Olympus America Inc., Melville, NY, USA) equipped with epiflouresence attachment and images were recorded using a digital camera with MagnaFireℱ 2.1 software.…”
Section: Immunohistochemistry and Fish Analysismentioning
confidence: 99%
“…Since H 2 O 2 can affect the analysis of PI3K activity, only hypoxia conditions (95% N 2 , 5% CO 2 ) were used when analyzing PI3K activity. Phosphorylation of Akt was measured by Western-blot as previously described [49]. Briefly, quiescent MSCs (10 6 ) were obtained by culturing cells in DMEM for 12 h. Cells were then treated with or without 250 nM 14S,21R-diHDHA under hypoxia conditions for 10 min, 2 h and 12 h, respectively.…”
Section: Phosphoinositide 3-kinase-akt Signalingmentioning
confidence: 99%